Synthesis and Characterization of Some New 1,3-Oxazepine and 1,3-Diazepine Derivatives Combined with Azetidine-2-one - Ruaa Wisam Adam (Journal of Global Pharma Technology, 2018)
This work involved prepared of some new series of chemical compounds of 1, 3-oxazepineand 1, 3-Diazepine derivatives. First step reaction of sulfadiazine with 4-amino acetophenone product of Schiff base (A) 4-((1-(4-aminophenyl) ethylidene) amino)-N-(pyrimidin-2-yl)benzenesulfonamide. Then, Schiff base [A] enter reactions with chloro acetyl chloride to product four-membrane ring  (B) 4-(2-(4-aminophenyl)-2-methyl-3-oxoazetidin-1-yl)-N-(pyrimidin-2-yl)benzene sulfonamide (B) were condensed with different aromatic aldehydes such as (p-hydroxybenzeldehyde, N,N-dimethylaminobenzeldehyde] in ethanol absolute   to give new Schiff  bases derivatives [B1-B2] respectively, Then the  resulting  imines  derivatives [B1-B2] were reacted  with  malic  anhydride  in toluene  to give new 1,3-oxazepine-4,7-dione ring derivatives [B1a-B2a] ,reaction 1,3-oxazepine[B2a] with Naphthyl amine to give 1,3-diazepine-4,7-dione ring derivatives[C].All compounds were characterized by M.P and FT-IR spectroscopy, some of them were characterized by 1H-NMR and C13NMR spectroscopy analysis.Keywords: Sulfadiazine, 4-aminoacetophenone, Azetidine-2-one, 1, 3-Oxazepine, 1, 3-Diazepine.